Melanin concentrating hormone and orexin shape social affective behavior via action in the insular cortex of rat - Barretto-de-Souza, Lucas [UNESP]; Joseph, Shemar A.; Lynch, Francesca M.; Ng, Alexandra J.; Chrsitianson, John P. (Cold Spring Harbor Laboratory, 2023)
ABSTRACT Rationale In a social context, individuals are able to detect external information from others and coordinate behavioral responses according to the situation, a phenomenon called social decision-making. Social decision-making is multifaceted, influenced by emotional and motivational factors like stress, sickness and hunger. However, the neurobiological basis for motivational state competition and interaction are not well known. Objective We investigated possible neural mechanisms through which internal states could shape social behavior in a social affective preference (SAP) test. In the SAP test, experimental rats given a choice to interact with naïve or stressed conspecifics exhibit an age-dependent preference to interact with stressed juvenile conspecifics, but avoid stressed adult conspecifics. First, we assessed the effect of hunger on SAP behavior. Behavior in the SAP test requires the insular cortex, which receives input from the hunger-related peptides melanin-concentrating hormone (MCH) and orexin neurons of the lateral hypothalamus (LH). This study aimed to evaluate the role of LH and insular MCH and orexin in SAP test. Methods SAP tests were conducted in rats that were sated, food deprived or allowed 1 h of access to food after 14 h of deprivation (relieved condition). Separate cohorts of sated rats received cannula implants for microinjection of drugs to inhibit the LH or to block or stimulate MCH or orexin receptors in the insula prior to SAP tests or social interaction tests. Results Food and water deprivation prior to SAP tests with juvenile rats caused a shift in preference away from the stressed rat toward the naïve juveniles. Pharmacological inhibition of LH with muscimol (100 ng/side) abolished the preference for the juvenile stressed conspecific, as well as the preference for the adult naïve conspecific. The blockade of MCHr1 or orexin receptors in the insular cortex with SNAP94847 (50µM) or TCS1102 (1µM), respectively, also abolished the preference for the stressed juvenile conspecific, but only the antagonism of orexin receptors was able to abolish the preference for the adult naïve conspecific. Microinjection of increasing doses (50 or 500 nM) of MCH or orexin-A in the insular cortex increased the interaction time in the one-on-one social interactions test with juvenile conspecifics, however only the microinjection of orexin-A increased the interaction time with adult naïve conspecifics. Conclusions Taken together, these results suggest that lateral hypothalamus peptides shape the direction of social approach or avoidance via actions MCH and orexin neurotransmission in the insular cortex.